Role of Helicobacter pylori in the Pathogenesis of Gastric Carcinoma and Progression of Lymphoid Nodules to Lymphoma - M Guindi (Canadian Journal of Gastroenterology)
The pathology of gastritis associated with Helicobacter pylori infection is summarized. The literature is reviewed regarding the role of H pylori in the pathogenesis of gastric carcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma. The potential mechanisms of gastric carcinogenesis include transformation of the gastric mucosa by metabolic products of H pylori, transformation of the host cell by incorporation of H pylori DNA and genotoxic effects of the inflammatory response to the organism. A model for gastric carcinogenesis is proposed in which H pylori causes cell proliferation, and the risk of DNA damage is increased, leading to inadequate repair and malignant transformation. Investigation of early gastric carcinomas concluded that two main pathways operated in gastric carcinogenesis, both starting from H pylori gastritis and leading to phenotypically variable gastric or intestinal tumour growth. The histological features and molecular genetics of MALT lymphoma are briefly reviewed. There is evidence that tumour cells of low grade B cell MALT lymphoma proliferate specifically in response to H pylori. This response is dependent on T cell activation by H pylori. A proposed model for the pathogenesis of MALT lymphoma postulates that B lymphocytes with a genetic change acquire a growth advantage resulting in a monoclonal proliferation in response to H pylori-activated T cells. Further genetic changes may result in escape from T cell dependency.